086 The big meet up – finding what is important to young healthcare users in england. (December 2018) - James, E; Sutton, A
Abstract : We would like to share the story of the Big Meet Up 2018 which was the first ever event organised by young people from Great Ormond Street Hospital, for young people at other paediatric hospitals and units. The event identified the biggest issues facing young healthcare users across England, something that has never been achieved before. More than 80 young people came together on Saturday 14 October 2017. The morning kicked off with laughter at a Q and A session with comedian and former GOSH patient Alex Brooker. Alex shared positive memories of his time at GOSH and told young people that they play an important part in their healthcare and if they stay quiet, they will not be able to have an impact. At the next session, young people were divided into groups, which mixed up ages and youth forums, for a 'share and steal' activity. Patients shared their thoughts on the rights of children and young people in healthcare, as well as practical issues and emotions of children and young people in hospital. At the end of the day, attendees chose a workshop to participate in. They could choose from a tour of GOSH, first aid and CPR training, a course on advocating for themselves, public speaking skills and more. To close the day, everyone voted on the issue to be taken forward by the NHS Youth Forum (which works with the Department of Health on national issues). The winning topics were: Everyday mental wellbeing should be everyone's responsibility and that Communication should be a two-way conversation amongst equals. Excitingly, the Nottingham University Hospitals Youth Service and Derby Teaching Hospitals Kite Team have agreed to co-host the next Big Youth Forum Meet Up in 2018. A video of the Big Meet Up is available at goo.gl/fzVpkj